2003
DOI: 10.1002/chem.200305001
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Photochemical C2–C6 Cyclisation of Enyne–Heteroallenes

Abstract: Herein we discuss computations that explain experimental results regarding a highly efficient triplet analogue of the C(2)-C(6) cyclisation of enyne-heteroallenes recently discovered by Schmittel and co-workers.1 To shed some light on the reasons for the differences found between enyne-carbodiimides, enyne-ketenimines and enyne-allenes, we have computed the reaction profiles of the C(2)-C(6) and of the C(2)-C(7) cyclisations for various model compounds, assuming that the reactions take place on the lowest-lyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 90 publications
2
10
0
Order By: Relevance
“…These cyclizations occur very effectively along the C 2 −C 6 , but interestingly not along the C 2 −C 7 (Myers−Saito) path. Theoretical studies by Engels explained the preference for the C 2 −C 6 route and suggested, as did our experimental results, that the process is initiated by triplet sensitization. Moreover, for a photochemical enyne−allene cyclization to be successful, the study recommended to avoid benzannulated derivatives due to their high excitation energy .…”
supporting
confidence: 81%
“…These cyclizations occur very effectively along the C 2 −C 6 , but interestingly not along the C 2 −C 7 (Myers−Saito) path. Theoretical studies by Engels explained the preference for the C 2 −C 6 route and suggested, as did our experimental results, that the process is initiated by triplet sensitization. Moreover, for a photochemical enyne−allene cyclization to be successful, the study recommended to avoid benzannulated derivatives due to their high excitation energy .…”
supporting
confidence: 81%
“…As to what concerns the latter processes, they may constitute an interesting terra incognita for nonstatistical dynamic effects as well. Because the photochemical initiation of the C 2 –C 6 cyclization of enyne–allenes via triplet excited states has equally been identified to be controlled by nonstatistical effects, the well established photocyclization of enyne–(hetero)allenes may open further interesting venues for studying nonstatistical behavior.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Heteroatomsubstituted enyne-allene analogues undergo similar cyclizations, as in the case of the aza-Myers reaction 32 or in the Moore cyclization of enyne-ketenes (1d, Scheme 2d). 33 Similar processes take place in enyne-isocyanates, 34 enyne-ketenimines 35 and enynecarbodiimides. 36 The Schmittel reaction (occurring in enyneallenes via a C 2 -C 6 mode) gives a non-aromatic biradical, [37][38][39][40] but several examples describe a subsequent intramolecular reaction involving a phenyl-substituent, likewise leading to benzocondensed aromatics.…”
Section: Introductionmentioning
confidence: 93%